Toothpaste Formulation Combination of Andaliman Fruit and Kecombrang Flowers as a Cleaner and Antibacterial - Gunawan, Muhammad; Safriana, Safriana; Andilala, Andilala; Fitriani, Enny (Newinera Publisher, 2024)
Currently on the market there are many circulating toothpastes for cleaning teeth and treatment, but they contain synthetic chemicals that can cause health problems, such as fluoride and sodium lauryl sulfate (SLS). This material can irritate the gums and mouth, gums feel burning, sensitive teeth and discomfort on the tongue. Traditionally, andaliman fruit has been used as a refreshing and deodorizing agent and prevents tooth decay by gargling for about 10 minutes. One natural ingredient that has been proven to have antibacterial activity and has often been used to eliminate bad breath and body odor is combrang flower (Etlinger elatior Jack). Therefore, the author utilizes the combination of andaliman fruit and combrang flowers in toothpaste formulations with the aim of obtaining a natural toothpaste that is relatively safe and economical. The formulation of toothpaste preparations uses a combination of andaliman fruit and combrang flowers concentrations of 2.5%, 5%, and 10% with a ratio (75:25); (50:50); and (25:75). Evaluation of the preparation includes tests of homogeneity, pH, stability, cleaning power, organoleptic with hedonic test, irritation test of volunteer skin, and antibacterial activity against mutant Streptococcus and Escherichia coli. Toothpaste preparations containing a combination of dry pollen of combrang flowers and andaliman fruit have good cleaning power, no irritation, and can eradicate Streptococcus mutans and Escherichia coli bacteria with strong categories. The best formula is with the content of combrang flowers and andaliman fruit 75:25, because although the cleaning power is smaller, it has the strongest antibacterial, so the resulting toothpaste provides benefits for cleaning and dental care, safe and economical.